Analysis of the attractiveness of the fortress landscape of Warsaw Fortress in the context of a contemporary city - Justyna Jastrzębska; Ewa Zaraś (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The Warsaw Fortress, built in the 19th century, constitutes an important element of the historical heritage of the Polish capital. However, as the city has developed, its role and significance have changed. The aim of this analysis is to understand the factors influencing the attractiveness of this landscape area in today’s times and the challenges facing its preservation and protection.